A Preliminary Result Of Air Quality Identification And Analysis Of Pm10 And Pm2.5 In Steel Industrial Area, Cilegon, Banten - Setiawati, Ira; Ermawati, Rahyani; Kang, Kitai; Chang, Insoo; Hong, Kihwan; Ervina, Ervina; Ariani, Auliyah; Fauzi, Ilham; Syah, Indra Lukman; Sefriana, Fita; Sari, Yessy Komala (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2019)
The increasingly rapid industrial development has produced pollutants in the form of gases and particles polluting the atmosphere. One of them is the steel industry where the majority of the air pollutants produced is particulate matter. Monitoring the air quality of particulate matter needs to be done routinely to identify and control the effects of air pollution somewhere. The purpose of this study is to identify and analyze particulate matter (PM10 and PM2.5) in the steel industry area in Cilegon, Indonesia. Ambient particulate matter is sampling by low-volume Sequential Particulate Matter (PM) Sampler with flow rate 5-20 L/minute for 24 hours per day in 4 months from September 2018 to January 2019. The results of identification and analysis of PM10 and PM2.5 in the steel industry area, Cilegon, Indonesia showed concentrations that varied greatly depending on sampling location conditions, with an average concentration range of 89.38 - 141.13 µg/m3 for PM10 and 21.74 - 50.69 µg/m3 for PM2.5.